Computer vision, imaging and computer graphics -- theory and applications : International Joint Conference, VISIGRAPP 2013, Barcelona, Spain, February 21-24, 2013, Revised Selected Papers /: International Joint Conference, VISIGRAPP 2013, Barcelona, Spain, February 21-24, 2013, Revised Selected Papers. (2020) - Unknown
No abstract available